PRODUKSI PAKAN FUNGSIONAL MENGANDUNG TIGA SENYAWA BIOAKTIF DARI AMPAS TAHU DENGAN MENGGUNAKAN Mikroba Effective Microorganism-4 DAN Lactobacillus plantarum - Budi Santosa; Eka Fitasari; Gatut Suliana (BUANA SAINS, 2017)
Tofu waste is a waste product from tofu processing which is known as high protein sources. Its use as feed has a problem due to the antinutrient content and lower amino acids. Effective microorganism (EM4) is a mixture of some microbes that are used to improve the quality of feed. Lactobacillus plantarum is facultative bacteria heterofermentatif group that has a high ability to ferment carbohydrates. The purpose of this study was to determine the effectiveness of both of these bacteria to ferment tofu waste and its influence on the increase in the content of nutrients and amino acids. This study used a Random Nested Design with 2 factor: Factor 1 was type of microbe (EM4 and Lactobacillus plantarum), factor 2 was the concentration of microbes which consists of 5 levels (1%, 5%, 10%, 15%, and 20% , v / w), each treatments was repeated 3 times. The results showed that the average treatment gave very significant effect on dry matter, anorganic matter, crude fiber, crude protein and had significant effect on crude lipid and gross energy. The treatments of 20% concentration of Lactobacillus plantarum giving highest yield on gross energy, crude fiber, calcium and fosfor.